Bronchial Artery Embolization in Management of Hemoptysis in a Developing Country: An Initial Experience - Puneet Garg; Ayush Khandelwal; Krishna Bhardwaj; Pranav Ish; Rajat Khurana; Amita Malik (The Arab Journal of Interventional Radiology)
Objectives This article evaluates the immediate success, recurrence rate, complications, and the culprit vessel of bronchial artery embolization (BAE) in patients presenting with hemoptysis. Materials and Methods All patients who underwent BAE from July 1, 2018 to August 31, 2021 were included. BAE was done for moderate to severe hemoptysis or for mild hemoptysis which was recurrent and not controlled by medical management. Patients referred for surgical intervention and hemoptysis controlled on medical management were excluded. Results One hundred and thirty patients underwent BAE in the study period. Mean age was 41.5 years and majority (73.1%) was male. Forty-three (33.1%) patients had mild, 46 (35.4%) had moderate, and 41 (31.5%) with the duration of symptoms ranging from 3 days to 25 years. Most common culprit vessel was posterior intercostal artery closely followed by the intercostobronchial artery. Hypervascularity was the most common angiographic abnormality encountered. On an average, 2.75 vessels were embolized per BAE with a wide range of 1 to 8 vessels. Hemoptysis control was seen in 96.1% patients immediately, 90.7 % at 1 month, 82.3 % at 3 months, and 66.9 % at 6 months. Overall recurrence was seen in 43 patients (33.1%). Chest pain was the most common minor side effect occurring in 77.1% cases. Conclusion BAE is a safe and effective procedure that can be performed routinely in patients presenting with moderate to massive hemoptysis or with mild hemoptysis refractory to medical management.